Journeys and metaphors; Some preliminary observations about the natural world of seashore and forested mountains in epic kakawin - Worsley, Peter (UI Scholars Hub, 2022)
In earlier publications I have argued that ancient Javanese poets imagined the world to be one marked by distinctions between a social world consisting of palace (kaḍatwan) and countryside (thāni-ḍusun) and a wilderness of seashores and forested mountains (pasir-wukir). The social world was characterized by the presence of an effective royal authority; the wilderness by its absence. A distinction was also drawn between this world inhabited by human beings and a world in which gods, ancestral spirits, and other divine beings dwelt (kedewatan). Journeys through these landscapes are an enduring interest in the narrative literature in the literary tradition of ancient Java and Bali. Margaret V. Fletcher (1990, 2002, 2021), Tony Day (1994), Helen Creese (1998), Raechelle Rubinstein (2000), and Peter Worsley (2012b, et al. 2013) have argued that the accounts of journeys in epic kakawin and other related works are not just tales of travel between one physical place and another. Rather, they are accounts of other kinds of journeys: the “journeys” which poets seeking inspiration make or which ascetics seeking apotheosis with their iṣṭadewata undertake or those on which young men and women transitioning from childhood to adulthood embark. In this essay, I make some preliminary observations about passages describing journeys in the natural world in a diverse selection of works authored between the twelfth and eighteenth centuries in Java and Bali and discuss aspects of the metaphorical referencing of these descriptions.